2011
DOI: 10.3791/2138
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and Ground Reaction Force Determination: A Demonstration Quantifying Locomotor Abilities of Young Adult, Middle-aged, and Geriatric Rats

Abstract: Behavior, in its broadest definition, can be defined as the motor manifestation of physiologic processes. As such, all behaviors manifest through the motor system. In the fields of neuroscience and orthopedics, locomotion is a commonly evaluated behavior for a variety of disease models. For example, locomotor recovery after traumatic injury to the nervous system is one of the most commonly evaluated behaviors [1][2][3] . Though locomotion can be evaluated using a variety of endpoint measurements (e.g. time tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 55 publications
(50 reference statements)
2
19
0
Order By: Relevance
“…This running speed range was consistently reached over a large portion of the maze (Fig. 1A–C), in agreement with other studies using similar behavioral settings [21]–[25], and was associated with trotting (not shown), as expected from kinematic studies of rat locomotion [25]. We next performed a power spectrum analysis of the acceleration signal during slow (speed<10 cm/s), intermediate (10–50 cm/s) and fast running speeds (50–110 cm/s).…”
Section: Resultssupporting
confidence: 92%
“…This running speed range was consistently reached over a large portion of the maze (Fig. 1A–C), in agreement with other studies using similar behavioral settings [21]–[25], and was associated with trotting (not shown), as expected from kinematic studies of rat locomotion [25]. We next performed a power spectrum analysis of the acceleration signal during slow (speed<10 cm/s), intermediate (10–50 cm/s) and fast running speeds (50–110 cm/s).…”
Section: Resultssupporting
confidence: 92%
“…Noxious light may also be used to prompt movement [74], though its effects on gait selection in rodents are currently unknown. Similarly, the effects of a positive cue on gait sequences, such as food reward or return to a home cage [75], are largely unknown, and it is not yet clear whether positive cues will alter the sensitivity of gait compensations relative to voluntary exploration.…”
Section: Considerations For Rodent Gait Characterizationmentioning
confidence: 99%
“…As in humans, skin markers have been used to describe the 3-D motion of a rat [75, 78]. These markers are used to approximate kinematic variables such as joint position and joint angles.…”
Section: Considerations For Rodent Gait Characterizationmentioning
confidence: 99%
“…Several studies that report changes in temporal parameters following injury only compare to a pre-surgical baseline or uninjured control group, suggesting that these measures are sensitive enough to detect differences above a given functional threshold (Giszter et al, 2008; Hampton et al, 2011; Vrinten and Hamers, 2003). The decreased sensitivity of temporal gait parameters may lead investigators to conclude that there is no effect of a treatment when a difference does indeed exist but cannot be detected (type-II statistical error) (Webb et al, 2011). Interestingly, Kale et al demonstrated a dose-dependent functional response to ethanol in mice with respect to stance, propulsion, and braking times, indicating that analysis of temporal parameters alone may be adequately sensitive for some applications (Kale et al, 2004).…”
Section: Discussionmentioning
confidence: 99%